"Nose-metrics" of wild southern elephant seal (Mirounga leonina) males using image analysis and geometric morphometrics - Andrea Cardini; Simona Sanvito; Maria Chiara Vinesi; Filippo Galimberti (Journal of Zoological Systematics and Evolutionary Research, 2019)
n/a